Barriers to cataract surgeries as perceived by visually impaired 50 years and older cataract blind participants of Nepal survey for rapid assessment of avoidable blindness. - Ranjan Shah; Sailesh Kumar Mishra; Rajiv Khandekar; Parikshit Gogate; Yuddha Dhoj Sapkota; Reeta Gurung; Mohan Krishna Shrestha; Islay Mactaggart; Ian McCormick; Brish Bahadur Shahi; Matthew Burton (PLoS ONE, 2025)
Purpose To identify the main barriers and determinants to cataract surgery as perceived by 50 years and older Nepali people with severe visual impairment & blind due to cataracts. Methods This was part of the Rapid Assessment for Avoidable Blindness (RAAB), held in all provinces of Nepal from 2018 to 2021. Cataract blindness was defined as a person having the best-corrected vision, < 6/60 in the better eye, and an unoperated cataract, which was the principal cause of visual disability. The participants were interviewed using a pretested questionnaire with seven known barriers. The demographic information was correlated with the barrier score. Results We surveyed 718 cataract blind. Two-thirds of the participants were females. Four in ten were aged 50-59 years. The main barriers perceived were 'need is not felt' (237; 33%), cost associated with surgery (218; 30%), lack of access (93; 13%), fear of surgery (88; 12%), nobody to accompany (40; 6%), unaware of surgery (18; 3%), and treatment denied (24; 3%). The barriers were not significantly different in females than in males. (P = 0.85). The provincial variations of barriers were significant. (P < 0.001). High cost was a perceived barrier in all provinces except Gandaki. Access to treatment was a barrier in the Gandaki province (38%). One in four participants in the Madhesh and Bagmati provinces feared surgery. Nearly half of the cataract blind in the Madhesh and Lumbini province did not feel 'need for restoring vision'. Conclusions To improve cataract surgery uptake, identified barriers, like lack of awareness, low visual need, and high cost must be addressed. The strategies could be devised according to provincial barriers but similar to both genders and all 50 years and older cataract blind. Offering low-cost cataract surgery, financial assistance and health promotion to improve awareness and remove fear were recommended.